Effect of power training on physical functional performance of patients with Parkinson's disease: A systematic review and meta-analysis of randomized controlled trials. - Samuel Brito de Almeida; Emmanuelle Silva Tavares Sobreira; Charles Phillipe de Lucena Alves; Danielle Pessoa Lima; Janine de Carvalho Bonfadini; Manoel Alves Sobreira-Neto; Thiago Holanda Freitas; Simony Lira do Nascimento; Pedro Braga-Neto (PLoS ONE)
Introduction Parkinson's disease (PD) is becoming more prevalent, highlighting the urgency of developing treatments to minimize its effects on muscular strength and physical function. Power training (PT) is a potential approach that may improve endurance and muscular power, essential for maintaining functional ability in PD. Objective To compare the effect of PT versus control or other physical activity (PA) interventions on physical functional performance (PFP) in PD patients. Methods We searched PubMed, MEDLINE, Embase, LILACS, PEDro, Cochrane Library, and Scopus. Inclusion criteria were randomized controlled trials comparing PT to a control group or another PA intervention in PD patients. PFP was the primary outcome. Pooled effect estimates were calculated from baseline to endpoint scores. Results From 21,558 results, four studies were included in the meta-analysis due to their moderate to high methodological quality. PT showed no significant effect on PFP outcomes compared to control groups (TUG: ES, -0.281; 95% CI, -0.693 to 0.130; P = 0.180; I2:0%; PWS: ES, 0.748; 95% CI, -0.768 to 2.265; P = 0.333; I2:88%; FWS: ES, 0.420; 95% CI, -0.950 to 1.791; P = 0.548; I2:83%; SLS: ES, 0.161; 95% CI, -0.332 to 0.655; P = 0.521; I2:0%). No differences were found between PT and alternative interventions (TUG: ES, 0.132; 95% CI, -0.394 to 0.657; P = 0.623; I2:0%; BBA: ES, 0.057; 95% CI, -0.430 to 0.544; P = 0.820; I2:0%). Conclusion PT did not improve PFP compared to control or alternative interventions. More studies are needed to explore PT effects (e.g., higher volume, intensity, and combined types) in PD patients.